Symbiotic formulation in experimentally induced liver fibrosis in rats: intestinal microbiota as a key point to treat liver damage? - D'Argenio, Giuseppe; Cariello, Rita; Tuccillo, Concetta; Mazzone, Giovanna; Federico, Alessandro; Funaro, Annalisa; De Magistris, Laura; Grossi, Enzo; Callegari, Maria L.; Chirico, Marilena; Caporaso, Nicola; Romano, Marco; et al. (Liver international, 2013)
Aim Evidence indicates that intestinal microbiota may participate in both the induction and the progression of liver damage. The aim of our research was the detection and evaluation of the effects of chronic treatment with a symbiotic formulation on CCl4‐induced rat liver fibrosis. Results CCl4 significantly increased gastric permeability in respect to basal values, and the treatment with symbiotic significantly decreased it. CCl4 per se induced a decrease in intestinal permeability. This effect was also seen in fibrotic rats treated with symbiotic and was still evident when normal rats were treated with symbiotic alone (P < 0.001 in all cases). Circulating levels of pro‐inflammatory cytokine TNF‐α were significantly increased in rats with liver fibrosis as compared with normal rats, while symbiotic treatment normalized the plasma levels of TNF‐α and significantly enhanced anti‐inflammatory cytokine IL 10. TNF‐α, TGF‐β, TLR4, TLR2, iNOS and α‐SMA mRNA expression in the liver were up‐regulated in rats with CCl4‐induced liver fibrosis and down‐regulated by symbiotic treatment. Moreover, IL‐10 and eNOS mRNA levels were increased in the CCL4+symbiotic group. Symbiotic treatment of fibrotic rats normalized serum ALT, AST and improved histology and liver collagen deposition. DGGE analysis of faecal samples revealed that CCl4 administration and symbiotic treatment either alone or in combination produced modifications in faecal profiles vs controls. Conclusions Our results provide evidence that in CCl4‐induced liver fibrosis, significant changes in gastro‐intestinal permeability and in faecal flora occur. Treatment with a specific symbiotic formulation significantly affects these changes, leading to improvement in both liver inflammation and fibrosis.